The Role of Combining Probiotics in Preventing and Controlling Inflammation: A Focus on the Anti-Inflammatory and Immunomodulatory Effects of Probiotics in an In Vitro Model of IBD - Shadi Aghamohammad; Amin Sepehr; Seyedeh Tina Miri; Saeideh Najafi; Mohammad R. Pourshafie; Mahdi Rohani (Canadian Journal of Gastroenterology and Hepatology)
Objective. IBD is an inflammatory disease with abnormalities such as dysbiosis and abnormal immune system activity. Probiotics, as live beneficial microorganisms, play a role in maintaining health through various mechanisms, including the modulation of the immune system and the control of inflammation. Here, we aimed to investigate the efficacy of a probiotic mixture of Lactobacillus spp. and Bifidobacterium spp. in modulating JAK/STAT and NF-kB inflammatory signaling pathways. Method. A quantitative real-time polymerase chain reaction (qPCR) assay was conducted to analyze the expression of JAK/STAT and inflammatory genes after treatment with the probiotic mixture before, after, and simultaneously with the sonicated pathogen in the HT-29 cell line. The production of IL-6 and IL-1β after probiotic treatment was investigated via cytokine assay. Results. Treatment with probiotics resulted in downregulation of TIRAP, IRAK4, NEMO, and RIP genes in the NF-kB pathway and JAK/STAT genes compared with sonicat-treated cells as inflammation inducers. The production of IL-6 and IL-1 decreased after probiotic treatment. Conclusions. The probiotic mixture of Lactobacillus spp. and Bifidobacterium spp. showed anti-inflammatory effects by modulating JAK/STAT and NF-kB signaling pathways. The use of probiotics could be considered as an appropriate complementary treatment for patients with inflammatory bowel disease.